2019
DOI: 10.1021/acs.macromol.9b01218
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Liquid Crystal Oligomer Phase Transitions: Toward Molecularly Engineered Shape Changing Materials

Abstract: This work details an integrated investigation of liquid crystal (LC) oligomers that combines experiments and molecular dynamics simulations to obtain a detailed understanding of the molecular structure of LC oligomers and the mechanism underlying their phase transition temperatures. We synthesized and characterized a series of LC oligomers prepared from different lengths of methylene spacers in the reactive LC monomers and n-alkylamine chain extenders via the aza-Michael addition reaction. In parallel, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Recent literature reports have documented the reduction in the thermotropic actuation of LCE by adjusting the length of the amine in the chain extended oligomer (in aza‐Michael addition) [ 30 ] or by utilizing mixtures of C6M with other liquid crystalline monomers (such as C3M). [ 25,31 ] These prior works are indirect approaches to disrupt the strength of the mesogen–mesogen interaction in molecular pairs that form in the LCE polymer network. Here, informed by the data in Figure 2, we examine the thermotropic actuation of TM LCE ( Figure a) prepared with C6BAPE (TM‐a), a 1:1 f.g. mixture of C6BAPE:C6M (TM‐b), or C6M (TM‐c).…”
Section: Resultsmentioning
confidence: 99%
“…Recent literature reports have documented the reduction in the thermotropic actuation of LCE by adjusting the length of the amine in the chain extended oligomer (in aza‐Michael addition) [ 30 ] or by utilizing mixtures of C6M with other liquid crystalline monomers (such as C3M). [ 25,31 ] These prior works are indirect approaches to disrupt the strength of the mesogen–mesogen interaction in molecular pairs that form in the LCE polymer network. Here, informed by the data in Figure 2, we examine the thermotropic actuation of TM LCE ( Figure a) prepared with C6BAPE (TM‐a), a 1:1 f.g. mixture of C6BAPE:C6M (TM‐b), or C6M (TM‐c).…”
Section: Resultsmentioning
confidence: 99%
“…The numberaverage molecular weight (M n ) of the humidity-responsive LC oligomer (h-LCO) after chain extension was 6900 g mol −1 , as determined by 1 H NMR end-group analysis, similar to our previous report (Figure S1, Supporting Information). [27] To prepare a monodomain h-LCE (i.e., a planar-aligned h-LCE), the reactions were performed inside a surface-aligned cell, as shown in Figure 1b. The gel fraction of the h-LCE was 90%, suggesting sufficient crosslinking.…”
Section: Synthesis and Characterization Of Liquid Crystal Elastomersmentioning
confidence: 99%
“…To investigate the effect of isomeric amine chain extenders on the thermal, mechanical, and actuation properties, we prepared a set of LCEs with a similar degree of crosslink density (i.e., a similar molecular weight (MW) of LCOs between the crosslinks). In general, the key to determining the MW of LCOs synthesized by step-growth polymerization is the stoichiometric imbalance between the LC monomer and chain extender [36,40,41]. However, although the amine chain extenders examined in this study were primary amines, they showed different reactivities toward the diacrylate groups in the LC monomer during the aza-Michael addition reaction (i.e., n-butyl > isobutyl > sec-butyl), which is possibly because of the difference in steric hindrance [42].…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…The 1 H NMR spectra of LCE-N1, LCE-N2, LCE-I1, LCE-I2, and LCE-S1 and the integration values used to calculate the DP are shown in Figure 2. The M n values of the LCOs were determined by a protocol similar to that described in our previous report [40], and the values are listed in Table 1. Briefly, peaks b (6.40 ppm), c (6.13 ppm), and d (5.82 ppm) correspond to the six protons in the diacrylate end groups in the LCOs, while peak a (8.15 ppm) corresponds to the four aromatic protons in the repeating units.…”
Section: Molecular Characterizationmentioning
confidence: 99%
See 1 more Smart Citation